Myopic axial elongation in school children and the COVID-19 lockdown in Russia: the ural children myopia study - Bikbov, Mukharram; Kazakbaeva, Gyulli M.; Fakhretdinova, Albina A.; Tuliakova, Azaliia M.; Rakhimova, Ellina M.; Panda-Jonas, Songhomitra; Gilemzianova, Leisan I.; Garipova, Liana A.; Khakimov, Dinar A.; Jonas, Jost B. (PLOS ONE, 2023)
Background To explore an influence of the COVID-19-related lockdown on ocular axial elongation in school children in Russia. Methods The participants of the school-based Ufa Children Myopia Study in Ufa/Russia underwent, at baseline in 2019/2020 before the COVID-19 outbreak and after a COVID-19-related lockdown, a detailed interview and ophthalmological examination including laser interferometric biometry for axial length measurement. Results The study included 461 children (age:10.7±2.1 years;range:6.8-16.9 years). The mean follow-up was 1.41±0.33 years. Mean axial length at baseline was 23.96±0.95mm and 23.94±0.95mm in the right and left eyes, respectively. During the study period, annual axial elongation (right/left eyes) was 0.19±0.17mm/0.19±0.22mm. Before the COVID-19 lockdown, the age-dependent coefficient for axial length (ADCAL) for the right/left eyes was 0.21mm (95%CI:0.17,0.25)/0.20mm (95%CI:0.16,0.24). In children younger than 9.6 years (n = 157), annual axial elongation (right eyes) during the study period was larger than the ADCAL before the COVID-19 outbreak (0.29 mm (95%:0.00,0.66) versus 0.21 mm (95%CI:0.02,0.41)). In the groups aged 9.6 to 11.4 years (n = 148) and aged >11.4 years (n = 156), annual axial elongation during the study period was comparable to the ADCAL before the COVID-19 outbreak (0.18mm (95%CI:-0.07,0.46) versus 0.22mm (95%CI:-0.05,0.48), and (0.09mm (95%CI:-0.15,0.34) versus 0.14mm (95%CI:0.00,0.28), respectively). In children aged ≤9 years at study end, axial length at study end was 0.20 mm larger than axial length at baseline in the participants aged ≤9 years at baseline. Larger axial elongation during the study period was associated (multivariable analysis) with younger age (beta:-0.62;P<0.001), female sex (beta:0.21;P<0.001), longer study period (beta:0.22;P<0.001), and longer axial length at baseline (beta:0.28;P<0.001), and marginally, with less time spent outdoors (beta:-0.07;P = 0.06). Conclusions The COVID-19-related lockdown in the Russian city of Ufa was associated with a relatively minor increase in axial elongation, detected only in children aged <9.6 years.
Gesehen am 18.06.2024